A study on the factors that influence the decision to register as voters among FSPPP students of UiTM Malacca city campus / Ahmadulkuddus Husain and Ainna Farhana Omar - Husain, Ahmadulkuddus; Omar, Ainna Farhana (Faculty of Administrative Science and Policy Studies, 2013)
Through modernization era nowadays, Malaysian societies are more knowledgeable and heading towards civil society. Among the most important aspects of the citizens who live in a democratic country is to fulfil its obligations by voting during elections. Voting is a duty for every citizen and one of the platforms to choose the country's leadership. However, in today's scenario, statistics voters who are registered as voters are still low and also involve young people. This study right will touch on a few aspects that influence the decision of students to register to vote. The scope of this study is focusing to the FSPPP students because they are better exposed in terms of political science and policy studies.